Ultrastructural Morphology and Molecular Identification of Laemobothrion maximum Lice (Phthiraptera: Laemobothriidae) from Brahminy Kite (Haliastur indus) in India - Elangovan, Tamileniyan; Murugesan, Jeevitha; Annamalai, Latchumikanthan; Muthusamy, Veeraselvam; Venugopal, Arul; Rangasamy, Velusamy; Kallipatti Karupusamy, Ponnu Swamy (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Laemobothrion maximum is one of the largest known avian lice, predominantly parasitizing raptors but detailed morphological and  molecular studies from India are scarce. A juvenile Brahminy kite rescued was presented with active lice infestation to VCRI, Orathanadu  (TN, India). Lice were collected, morphologically examined and processed for scanning electron microscopy (SEM) and molecular  confirmation. Morphological examination identified the specimens as L. maximum, measuring 10-11 mm, with a flattened head,  sculptured temples, U-shaped sitophore sclerite, cephalic ctenidia and specialized tarsal claws. SEM revealed ultrastructural adaptations  including mandibular cuticular projections, diverse trichoid and basiconic sensilla, reticulated abdominal microtrichial patterns.  Molecular identification using mitochondrial cytochrome c oxidase subunit-I (COI) gene amplification confirmed species identity with  high accuracy. This is the first integrated morphological, ultrastructural and molecular description of L. maximum infesting Brahminy  kite in India. The findings provide insights into its identification features, host specificity and adaptive traits, offering a valuable baseline  for future taxonomic, ecological and phylogenetic studies on avian lice.
Keywords: Brahminy kite, Cytochrome c oxidase subunit-I (COI) gene, Electron microscopy, Laemobothrion, Morphometry, Sensilla